Four new species and new records of Macrostomus Wiedemann (Diptera: Empididae) from Northern and Northeastern Regions of Brazil - Sena, Jasmine Déa Nogueira; Rafael, José Albertino; Limeira-De-Oliveira, Francisco (Zootaxa, 2024)
Macrostomus Wiedemann is recorded for the first time in the Cerrado Biome and also from the state of Maranhão, Brazil. The following species are treated here: Macrostomus maranhensis sp. nov. and Macrostomus paraiba Rafael & Cumming (M. amazonensis species-group); Macrostomus ferrugineus (Fabricius) and Macrostomus gurupi sp. nov. (M. ferrugineus species-group), Macrostomus cummingi sp. nov. (M. pictipennis species-group) and Macrostomus paraensis sp. nov. (unplaced species-group). A map showing the distribution of these species is presented.